(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
The redox behavior, surface reaction kinetics, stability, electrolysis characteristics and efficiency of a Pd-20 at %Ni electrode have been investigated in 30wt.%KOH electrolyte at room temperature by using cyclic voltammetry. The electrode showed three couples of redox peaks in between the potential range -1.0 to + 0.65 V. The origin of the peak couples were identified by cycling Pd and Ni electrodes independently in the same potential ranges. It was realized that the peak couples were originated from the transformations of M(0) ←→ M(II) oxide, M(II) oxide ←→ M(III) oxide and M(III) oxide ←→ M(IV) oxide, respectively. The term M represents the Pd-Ni alloy. The potentials of the peaks, potential differences of the peak couples and the peak currents found remarkably different than those of Pd and Ni electrodes. The redox reaction kinetics of the electrode showed combined surface reaction trends of Pd and Ni electrodes. The apparent stability of the electrode found good. The electrode showed equal and 4.2 times higher oxygen evolution current densities than those of Ni and Pd electrodes. Hydrogen evolution current density found 2.9 times lower than that of Pd electrode but 100% better than the Ni electrode at the potential range - 1.0 to + 0.65 V. Almost 70% hydrogen evolution efficiency of Pd electrode was found at the potential range - 1.0 to - 0.05 V. On cycling the electrode at various potential ranges, it was found that the redox behavior resembled to that of Pd electrode at low potential ranges. The observed results indicated that Pd-20at.%Ni electrode is a good electrode during electrolysis for oxygen evolution reaction and its electrolysis efficiency is far better than the Ni electrode. Key words: Pd-20at. %Ni electrode, Redox behavior, Hydrogen evolution, Oxygen evolution. DOI: 10.3329.bjsir.v43i1.853 Bangladesh J. Sci. Ind. Res. 43(1), 13-28, 2008